2016
DOI: 10.1152/ajplung.00090.2016
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusα-toxin-mediated cation entry depolarizes membrane potential and activates p38 MAP kinase in airway epithelial cells

Abstract: Eiffler I, Behnke J, Ziesemer S, Müller C, Hildebrandt JP. Staphylococcus aureus ␣-toxin-mediated cation entry depolarizes membrane potential and activates p38 MAP kinase in airway epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 63 publications
2
29
0
4
Order By: Relevance
“…Experiments with HlgCB indicated that ion flux did not occur through toxin pores, but occurred indirectly through Na + /K + ATPases [152]. In Hla treated lung epithelial cells, K + efflux is sufficient to induce p38-MAPK signaling [153]. Similarly, K + efflux was responsible for initiating inflammasome activation in monocytes following LukAB intoxication [92].…”
Section: Cellular Effects Of Toxin Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments with HlgCB indicated that ion flux did not occur through toxin pores, but occurred indirectly through Na + /K + ATPases [152]. In Hla treated lung epithelial cells, K + efflux is sufficient to induce p38-MAPK signaling [153]. Similarly, K + efflux was responsible for initiating inflammasome activation in monocytes following LukAB intoxication [92].…”
Section: Cellular Effects Of Toxin Actionmentioning
confidence: 99%
“…Similarly, K + efflux was responsible for initiating inflammasome activation in monocytes following LukAB intoxication [92]. Other signaling pathways that are initiated by Hla-pore formation include the p38, Erk, and c-Fos signaling pathways, which are associated with inflammatory or immune signaling, as well as the initiation of cell survival pathways [153, 154]. In particular, the p38 pathway has been shown to be activated in cells treated with Hla-concentrations that were insufficient to induce detectable levels of cell death, indicating the sensitivity of the pathway [116].…”
Section: Cellular Effects Of Toxin Actionmentioning
confidence: 99%
“…Additionally, treatment of airway epithelial cells with recombinant α-hemolysin results in plasma membrane depolarization, and increased phosphorylation of paxillin and p38 MAP kinase, a signal transduction module involved in host defensive actions (Eiffler et al, 2016). Lastly, staphylococcal EsxA protein interferes with epithelial cell apoptotic pathways and, together with EsxB, mediates the release of intracellular staphylococci from the host cells (Truong-Bolduc et al, 2015).…”
Section: The Epithelial Surface As the First Line Of Defense Against mentioning
confidence: 99%
“…Treatment of cells with an rHla-variant (rHla-H35L), which is not able to form functional transmembrane pores [30], did not affect mitochondrial membrane potential. As exposure of airway epithelial cells to rHla results in calcium influx into the cytosol [31] and mitochondria are able to buffer cellular calcium loading by importing calcium ions into the mitochondrial matrix [32], we measured [Ca 2+ ] within the mitochondrial matrix using the fluorescent dye Rhod-2. As shown in Figure 2E, exposure of cells to 2000 ng/mL rHla resulted in an increase in [Ca 2+ ] m to approximately 250% of the initial value over a period of 40 min compared with the controls.…”
Section: Resultsmentioning
confidence: 99%
“…There are two possible explanations for this finding. The first is that rHla pore formation which has been shown to result in an influx of sodium and calcium ions into the cytosol, and plasma membrane depolarization [31] reduces mitochondrial inner membrane potential and mitochondrial ATP production. This would lower the cellular ATP content per se without any effects on extracellular ATP.…”
Section: Discussionmentioning
confidence: 99%